Influence of abiotic drivers on 1‐year seedling survival of six mangrove species in Southeast Asia. Issue 8 (21st April 2022) - Sloey, Taylor M.; Lim, Kiah Eng; Moore, Jared; Heng, Jie Min; Heng, Jia Min; van Breugel, Michiel
Abstract : Establishment and survival of plant species in systems with dominant environmental drivers (i.e. factors that exert disproportionate control over species establishment and survival) is often thought to be dominated by one master variable. In forested wetlands such as mangroves, hydrology is typically considered the dominant limiting driver. At the same time, light is a major driver of plant community dynamics, with some of the best understood plant life‐history tradeoffs related to fast growth under high‐light conditions versus survival under low‐light conditions. Yet light is given relatively limited consideration in mangrove research compared to other drivers. Understanding the relative importance of abiotic drivers for seedling survival is crucial for effective management and restoration of mangrove ecosystems. Despite increasing global efforts to plant mangrove propagules at elevations appropriate for the hydrologic conditions needed at early life history stages, restoration efforts report low survival of planted propagules. Although many studies have made considerable progress to characterize the abiotic limitations of mangrove propagule establishment, fewer studies have addressed multiple abiotic drivers that limit the survival of the established seedling stage. We characterized the light and inundation conditions of more than 900 naturally established mangrove seedlings and monitored the survival of more than 2, 800 seedlings (including 16 species) located on a species‐rich island in tropical Southeast Asia for 1 year. Our findings suggest that light has a stronger effect than hydrology on survival following seedling establishment. We provide a conceptual visualization of shifts in the drivers of mangrove survival/loss throughout ontogeny.